IMPLEMENTASI PERMENKUMHAM NO 07 TAHUN 2022 DALAM MENGATASI OVERCROWDED NARAPIDANA KASUS TIPIKOR DI LAPAS KELAS I MAKASSAR - Siregar, Humala Mahmud Husen; Yuska, Syahrial (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Inmates serving sentences have rights protected by human rights and Indonesian law, one of which is the granting of remission. Remission is a reduction in the criminal term for qualified inmates, among others, behaving well but not convicted with the death penalty or life imprisonment. The prison manages the granting of these waivers. The remission is a form of systematic construction in correctional services used in Indonesia. Remission supports the reintegration into society or rebuilding good relations between inmates and the community. Provision of Remission to Inmates who have committed a special criminal offense under Government Regulation No. 99, 2012, was based on a sense of social justice. Currently, the procedure for granting remission for special criminal acts is regulated in the Regulation of the Minister of Law and Human Rights No. 7 of 2022 About the Terms and Procedures for Granting Remission, Assimilation, Family Visiting Leave, Parole, Leave Before Release, and Conditional Leave are very different from the previous regulations. Keywords: Inmates; Remissions; Special Crimes